Splatoon. Vol. 2 - Hinodeya, Sankichi; Haun, Jeremy; Hurley, Jason A., 1981- (VIZ Media, LLC, 2018)
Team Blue has done well so far in the Turf Wars, but the S4 inklings are preparing to bring Goggles and his friends down. The team must find a way to improve, and it might mean accepting help from an unlikely source.